2005
DOI: 10.1021/ie050012z
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Pressure Swing Adsorption and Fractionated Vacuum Pressure Swing Adsorption Processes for CO2 Capture

Abstract: This work focuses on the optimization of cyclic adsorption processes to improve the performance of CO 2 capture from flue gas, consisting of nitrogen and carbon dioxide. The adopted processes are the PSA (pressure swing adsorption) process and the FVPSA (fractionated vacuum pressure swing adsorption) process, modified from the FVSA (fractionated vacuum swing adsorption) process developed by Air Products and Chemicals, Inc. The system models are currently bench scale and adopt zeolite13X as an adsorbent. The hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
148
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(153 citation statements)
references
References 7 publications
5
148
0
Order By: Relevance
“…95,96 The removal of CO2 from flue gas streams may more efficiently be accomplished with solid state adsorbents such as activated carbons via either pressure swing adsorption (PSA) or vacuum swing adsorption (VSA) processes. 97,98 A typical PSA system may adsorb at a pressure of 6 bar and be recycled (i.e., desorb) at 1 bar, while for VSA systems, adsorption may occur at 1.5 bar and evacuation at ca. 0.05 bar.…”
Section: Working Capacity For Pressure-swing Adsorption (Psa) and Vacmentioning
confidence: 99%
“…95,96 The removal of CO2 from flue gas streams may more efficiently be accomplished with solid state adsorbents such as activated carbons via either pressure swing adsorption (PSA) or vacuum swing adsorption (VSA) processes. 97,98 A typical PSA system may adsorb at a pressure of 6 bar and be recycled (i.e., desorb) at 1 bar, while for VSA systems, adsorption may occur at 1.5 bar and evacuation at ca. 0.05 bar.…”
Section: Working Capacity For Pressure-swing Adsorption (Psa) and Vacmentioning
confidence: 99%
“…As proposed by Grande and Rodrigues (2008) for CO 2 adsorption, adsorbents with a greater adsorption capacity and higher heat of adsorption than the activated carbon honeycomb monolith should be used to achieve a product purity of greater than 16%. Although the CO 2 purity is lower than that is required to transport, the PSA cycle could be optimized in order to increase the CO 2 purity and recovery (Ko et al, 2005). Transport considerations limit the CO 2 purity > 95.5% to ensure a reasonable input of CO 2 compression power (Vinay & Handal, 2010).…”
Section: Fixed-bed Co 2 /N 2 Mixture Adsorption: Experimental Data Anmentioning
confidence: 99%
“…PSA is a cyclical process of adsorption/desorption that occurs through pressure changes and can be very suitable for carbon dioxide separation from exhaust gases due to its easy application in a large temperature range. The most studies presents the CO 2 /N 2 separation using PSA process at room temperature, but it has been reported that is possible to obtain high purity CO 2 (~90%) at high temperature (Ko et al, 2005). Recently, Grande and Rodrigues (2008) reported that it is possible to recover around 89% of the CO 2 from a CO 2 /N 2 mixture using honeycomb monoliths of activated carbon through ESA.…”
Section: Introductionmentioning
confidence: 99%
“…Within TSA technologies, the specific case in which the solid is heated by the Joule effect is commonly referred to as electric swing adsorption (ESA) [5,6]. The vast majority of studies dealing with CO 2 post-combustion capture by means of PSA or TSA technologies use zeolites as adsorbent [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Zeolite 13X is by far the adsorbent most extensively studied in CO 2 separation processes, due to its high selectivity to CO 2 [21].…”
Section: Introductionmentioning
confidence: 99%